Home sweet home: Comparison of epibiont assemblages associated with cultivated and wild sugar kelp (Saccharina latissima), co-cultivated blue mussels (Mytilus edulis) and farm infrastructure - Sophie Corrigan; A. Ross Brown; Charles R. Tyler; Catherine Wilding; Carly Daniels; Ian G. C. Ashton; Dan A. Smale (Journal of Applied Phycology, 2024)
Seaweed farming is expanding in Europe and may provide environmental benefits similar to those from natural kelp forests and shellfish farms, including habitat provisioning. Few studies have substantiated these claims however, and it remains uncertain whether seaweed farms will support similar biodiversity to kelp forests or provide valuable long-term habitat beyond the harvest season. We repeatedly surveyed an integrated sugar kelp ( Saccharina latissima ) and blue mussel ( Mytilus edulis ) farm in southwest UK to compare epibiont assemblages between cultivated kelps, to those from three nearby wild kelp populations, and to epibionts on farmed mussel lines and unseeded ‘bare’ lines. We found farmed kelps supported over 217 times the abundance of epibionts living on wild kelps at harvest time, however, taxonomic diversity per kelp was lower at the farm. Farmed kelp assemblages were dominated by amphipods, which were present on the wild kelps but in much lower numbers. Farmed kelp also supported distinct assemblages to cultivated mussels, which were similarly dominated by amphipods, but hosted higher relative abundances of crabs, echinoderms, worms and red algal biomass. The bare lines were heavily colonised by another pseudo-kelp, Saccorhiza polyschides , which supported similar epibiont assemblages to the seeded S. latissima lines. Our findings indicate that cultivating bivalves alongside seaweed can increase habitat provisioning at a seaweed farm and extend its permanence beyond typical seaweed cultivation periods as bivalves have longer, continuous farming periods. However, the presence of mussels will likely influence the epibiont assemblages on the farmed kelp, which are distinct from wild kelp populations.